Ultrasonic welding of lap joints of PEI plates with PEI/CF-fabric prepregs - Vladislav Alexenko; Defang Tian; Sergey Panin; Svetlana Bochkareva; Iliya Panov (Fracture and Structural Integrity)
In this study, ultrasonic welding (USW) of lap joints of polyetherimide (PEI) plates (adherends) with carbon fiber (CF) prepregs impregnated with PEI was investigated. No energy director (ED) was used, so binder contents were varied in the prepregs to compensate for the lack of the polymer in the fusion zone. In addition, the effect of the USW parameters on the structure and the mechanical properties of the lap-joints were analyzed. The most homogeneous macrostructure, the maintained structural integrity of both the CF-fabric in the prepregs and the lap-joined PEI adherends, as well as the maximum strength properties (tensile strength) were revealed for the USW joints with the minimum polymer content in the prepreg. In this case, rising the USW time from 400 up to 800 ms radically changed the macrostructure of the fusion zone, while the strength properties did not vary significantly (shear stresses were 42–48 MPa). Computer simulation of the influence of the PEI/CF-fabric ratios in the prepregs on the deformation response of the USW joints showed that the prepreg thicknesses and, accordingly, the PEI/CF ratios did not exert a noticeable effect on the strain–stress (tensile) diagrams, while the determining factor was the adhesion level.